2008
DOI: 10.1021/jm801033c
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent Scaffolds for Affinity Maturation of Small Molecule Cell Surface Binders and Their Application to Prostate Tumor Targeting

Abstract: Adamantane scaffolds for affinity maturation of prostate cancer specific ligands of low molecular mass are described. These scaffolds are modular and can be used for conjugation of up to three ligands and an additional effector molecule by standard peptide coupling techniques. The potential of the scaffolds is demonstrated with the multimerization of GPI 1, a prostate cancer specific small molecule. A detailed study of multimerized GPI conjugates with NIR-fluorophores and their binding properties to different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
61
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 51 publications
1
61
0
Order By: Relevance
“…[6][7][8] Such small symmetrical molecules are usually constructed on a corresponding symmetrical template.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] Such small symmetrical molecules are usually constructed on a corresponding symmetrical template.…”
mentioning
confidence: 99%
“…[3][4][5] With reference to the molecular symmetry, small molecules having C 3 -, C S -, or C 2 -symmetrical geometry frequently appear in various biologically active compounds. [6][7][8] Such small symmetrical molecules are usually constructed on a corresponding symmetrical template.…”
mentioning
confidence: 99%
“…[17][18][19] It has been shown that the (S,S) diastereoisomer of GPI is the eutomer with significantly higher affinity to the target protein than the corresponding (S,R) isomer. [20][21] However, the stereoselective synthesis of GPI proved to be difficult and only low diastereoselectivities have been realized so far.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4] Regarding the molecular symmetry, small symmetrical molecules with a C 2 -symmetrical or C 3 -symmetrical structure have often been found in various synthetic biologically active compounds. [5][6][7] In the course of our work on new antiviral compounds, we have presented a new class of antiviral candidates. For example, we have already reported that most of the triarylmethane derivatives showed a wide range of antiviral activities against herpes simplex virus type 1 (HSV-1).…”
mentioning
confidence: 99%
“…In the area of molecular recognition, a tripodal arrangement of cell-specific ligands is an ideal recoginition motif for cell surfaces, and it is known that a number of receptors share a common binding motif with three-fold symmetry. 7,[11][12][13][14] In order to find new promising candidates, we have chosen tris(2-aminoethyl)amine (TREA) as a new scaffold. TREA derivatives have been studied extensively in the field of coordination chemistry; however, little is known about their biological activities.…”
mentioning
confidence: 99%